Management of the Reading Corner Program in Improving Student Literacy and Competence at SDN Selaawi, Cianjur Regency - Nendi Wahyudi; R. Supyan Sauri; Abdul Holik, (Journal of Science and Education (JSE), 2025)
This study aims to describe the management of the reading corner program at SDN Selaawi, Cianjur Regency, in improving the literacy and competence of elementary school students. The research uses a qualitative approach with a case study method. The research subjects consisted of principals, teachers, and students. Data were collected through interviews, observations, and documentation studies, then analysed using the Miles and Huberman model. The study results show that the management of the reading corner program is carried out through the planning of literacy activities, the routine implementation of the program, and evaluation through the assessment of students' reading interest and literacy ability. The reading corner program has proven to impact improving students' literacy skills and basic competencies positively. However, there are still obstacles in providing reading materials and parental involvement. This research contributes to the development of literacy management in elementary schools and becomes an example of good practices for other schools that want to develop a literacy culture.